ANALISIS REPRESENTASI CHATBOT DALAM MEDIA SOSIAL, HIBURAN, DAN DAMPAKNYA TERHADAP BUDAYA DIGITAL - Syifa Mauliddia; Dian Indri Eklesia Lumban Tobing; Dwi Anggita (Jurnal Riset Sistem Informasi, 2026)
The development of chatbots today has shaped new ways for humans to interact in an all-digital environment. Chatbots are no longer understood as tools that simply answer simple questions, but have evolved into entities that are present and play a role in various digital spaces, from education, mental health, social media, entertainment, to pop culture communities. This study presents an overview to understand how chatbots are represented, used, and interpreted in digital culture. The findings indicate that chatbots increasingly play a role in emotional and social aspects, and make important contributions to shaping people's digital experiences. Various studies highlight how chatbots can support the learning process, facilitate information navigation, and provide emotional support for their users. Overall, these findings confirm that chatbots have become a significant element in modern digital life and open new spaces for discussions about ethics, the need for more context-sensitive design, and the development of technology that centers the human experience.